Depressive symptoms and alcohol use among adolescents - Pinto, Isabel C. (2010)
Alcohol is the most consumed substance by young people, sometimes it’s associated with depressive symptoms. Objective: Assess the factors associated with alcohol use among 13-year-old teenagers, like depressive symptoms. Methods: Data of a population-based cohort of urban teenagers included cross-sectional information of 919 boys and 1016 girls collected by self-reported questionnaire. Depressive symptoms were evaluated using Beck Depressive Inventory II (BDI). The Mann-Whitney test was used to compare medians. Odds ratio (OR) and multiple linear regression (β) were performed to estimate the magnitude of associations with 95% confidence intervals (95%CI). The final model was adjusted for parents’ education, sports, smoking, have friends who drink and parents’ history of depression. Results: Overall 515(50.0%) girls and 425(44.9%) boys have experimented alcoholic beverages and, 48(4.7%) girls and 62(6.6%) boys have drunk(one drink at least once time per month) at 13-year-old. For both genders, after adjustment, being experimenter was significantly associated with parents’ education, tobacco use and friends who drink. In girls, characteristics that was significantly associated to be drinker were tobacco use OR=6.9(3.1-15.2) and friends who drink OR=6.4(2.7-15.2). In boys, to be drinker was associated with tobacco use OR=5.9(2.7-13.0), friends who drink OR=7.3(3.5-15.4) and cohabiting with people who drink OR=5.1(1.4-17.6). Adolescents who have drunk presented a high score in BDI [median(25p-75p)] in girls[6.01(2.00-10.00)vs.6.38(3.00-11.99),p=0.002)] and in boys[3.00(1.01-6.01)vs.3.99(1.01-6.99),p=0.039]. After adjustment, the association was not significant in girls(β=0.583,95%CI[-0.483;1.648]) in boys(β=0.623,95%CI[-0.170;1.417]). Conclusions: Among 13-year-old adolescents parents’ education, smoking and friends who drink were associated with drinking behaviour. After adjustment, depressive symptoms did not show a significant association with alcohol use.